Предмет: Алгебра,
автор: nastyaalleksee
Функция задана формулой f(x)=x-5/2-x. Найдите f(-3)
Ответы
Автор ответа:
0
Для начала найдем производную функции:
![f(x)'= frac{(x-5)'*(2-x)*(2-x)'*(5-x)}{ (2-x)^{2} } = frac{(2-x)*(x-5)}{4-4x+ x^{2}}= frac{ x^{2}-7x+10}{ x^{2} -4x+4} f(x)'= frac{(x-5)'*(2-x)*(2-x)'*(5-x)}{ (2-x)^{2} } = frac{(2-x)*(x-5)}{4-4x+ x^{2}}= frac{ x^{2}-7x+10}{ x^{2} -4x+4}](https://tex.z-dn.net/?f=f%28x%29%27%3D+frac%7B%28x-5%29%27%2A%282-x%29%2A%282-x%29%27%2A%285-x%29%7D%7B+%282-x%29%5E%7B2%7D+%7D+%3D+frac%7B%282-x%29%2A%28x-5%29%7D%7B4-4x%2B+x%5E%7B2%7D%7D%3D+frac%7B+x%5E%7B2%7D-7x%2B10%7D%7B+x%5E%7B2%7D+-4x%2B4%7D+)
![f(3)'= frac{ 3^{2}-7*3+10}{ 3^{2}-4*3+4 }= frac{9-21+10}{9-12+4} = frac{-2}{1} =-2 f(3)'= frac{ 3^{2}-7*3+10}{ 3^{2}-4*3+4 }= frac{9-21+10}{9-12+4} = frac{-2}{1} =-2](https://tex.z-dn.net/?f=f%283%29%27%3D+frac%7B+3%5E%7B2%7D-7%2A3%2B10%7D%7B+3%5E%7B2%7D-4%2A3%2B4+%7D%3D+frac%7B9-21%2B10%7D%7B9-12%2B4%7D+%3D+frac%7B-2%7D%7B1%7D++%3D-2)
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: Аноним
Предмет: История,
автор: omelchenkoruta100
Предмет: Биология,
автор: dgrishina43
Предмет: Химия,
автор: dstolbova19975